Kilka uwag na temat wykorzystania zmiennych lingwistycznych w firmie - Baran, Paweł; Gnat, Sebastian (Several Remarks on Linguistic Variables Usage in Companies, 2007)
In the article some of the problems concerning fuzzy constraints and goals modeling are addressed. An example of finding the appropriate representation for some linguistic variables arising in a real enterprise investment model is discussed and a few hopefully useful remarks are given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 11-20